Toughening type polylactic acid blend as well as preparation method and application thereof
Modifying polylactic acid by melt blending method of specific ratios solves the problems of its brittleness and slow degradation speed, and achieves application expansion and environmentally friendly biodegradation efficiency in high stress scenarios.
Patent Information
- Application Number
- CN202411579396.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polylactic acid materials have problems such as high brittleness, poor toughness, lack of elasticity and slow degradation speed, which limits their application in high stress scenarios.
The specific ratio of polyp-dioxane, chitin, polymethyl acrylate, glycerol, polycaprolactone, propylene oxide and polymethyl methacrylate and polylactic acid are modified by melt blending. Improves its toughness and degradation speed.
It effectively improves the toughness and degradation speed of polylactic acid materials, and broadens its application prospects in automobile manufacturing, aerospace, electronic equipment, industrial equipment and packaging materials manufacturing.
Smart Images

Figure BDA0005122638450000021 
Figure BDA0005122638450000022 
Figure BDA0005122638450000031
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and in particular to a toughened polylactic acid blend and a preparation method and application thereof. Background Art
[0002] Polylactic acid (PLA) is a high molecular polymer made from green plants. It is made by decomposing the raw materials into glucose, fermenting them to generate lactic acid, and polymerizing the lactic acid. Its physical and chemical properties are similar to those of traditional thermoplastics. However, compared with traditional plastics, it has better biodegradability and will not cause pollution and damage to the environment, solving the energy consumption and environmental pollution problems caused by the processing of traditional plastics.
[0003] In addition to its excellent biodegradability, PLA's good processability and good mechanical properties have led to its extensive research and application. In the biomedical field, PLA can be used to produce disposable medical tools, which can reduce environmental pollution after disposal. Because of its certain biocompatibility and mechanical strength, it can be used to manufacture non-removable surgical sutures and artificial bone tissue. However, PLA materials have problems such as high brittleness, poor toughness, lack of elasticity, general fluidity and slow degradation. These defects limit many industrial applications of PLA, especially industrial and medical applications that require good plastic deformation capabilities under high stress levels. Therefore, in order to further broaden the scope of application of PLA, it is necessary to perform appropriate physical or chemical modifications on it so that it can meet different usage requirements.
[0004] There are many PLA modification schemes in the prior art, such as:
[0005] Chinese patent CN110204876A discloses a modification method for strengthening and toughening polylactic acid. The polylactic acid material is modified by melt blending a sulfonated polystyrene ionomer containing a sulfonated rigid segment and a thermoplastic elastic flexible segment with polylactic acid, and the strengthening and toughening effect is achieved at the same time. Sulfonated polystyrene ionomers are polystyrene block copolymers such as poly (styrene-butadiene-styrene) (SEBS) and the like, obtained by sulfonating polystyrene segments to varying degrees, wherein the flexible segments play a role in toughening the polylactic acid composite material.
[0006] Chinese patent CN102675523B discloses a polylactic acid toughening agent and a preparation method thereof, a modified polylactic acid and a preparation method thereof, wherein the preparation method of the polylactic acid toughening agent comprises the following steps: (1) adding methyl acrylate and polymethyl methacrylate to a first emulsifier to obtain a first mixture; (2) adding a first initiator to the first mixture to initiate a reaction, removing the condensate generated in the reaction, and obtaining a second mixture; (3) adding a second emulsifier to the second mixture, and then adding a third mixture, wherein the third mixture is composed of methyl acrylate, a dispersant, a second emulsifier, a second initiator and water, and continuing the reaction to obtain an emulsion; (4) diluting the emulsion, adding a demulsifier, heating and coagulating, and drying the precipitate to obtain a polylactic acid toughening agent. The preparation method is simple, the prepared polylactic acid toughening agent has good compatibility with polylactic acid, and the amount of additives used in the modified polylactic acid obtained therefrom is reduced, thereby improving the utilization rate of polylactic acid.
[0007] Among them, blending is a common method for polymer modification, which has the advantages of simple method, low cost and easy operation. Blending modification of polylactic acid can make PLA obtain more ideal comprehensive properties and greatly broaden the application range of polylactic acid. In order to improve the toughening efficiency of polylactic acid, more polylactic acid toughening methods need to be further developed. Summary of the invention
[0008] The purpose of the present invention is to provide a toughened polylactic acid blend and a preparation method and application thereof, which can effectively improve the toughness of polylactic acid and simultaneously increase its degradation rate.
[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0010] The present invention provides a toughened polylactic acid blend, which is made from the following raw materials in parts by weight:
[0011]
[0012] Preferably, it is made from the following raw materials in parts by weight:
[0013]
[0014]
[0015] The present invention also provides a method for preparing the toughened polylactic acid blend, comprising the following steps:
[0016] All materials are blended to obtain a toughened polylactic acid blend.
[0017] Preferably, the blending is performed by melt blending.
[0018] Preferably, the equipment used in the melt blending method is an internal mixer.
[0019] Preferably, the temperature of the melt blending method is 130-180°C.
[0020] Preferably, the melt blending process is carried out for 10 to 30 minutes.
[0021] Preferably, the rotation speed of the melt blending method is 20 to 40 rpm.
[0022] Preferably, the blending further comprises extrusion molding;
[0023] The thickness of the extrusion molding is 0.1 to 10 mm.
[0024] The present invention also provides the use of the toughened polylactic acid blend or the toughened polylactic acid blend prepared by the above preparation method in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.
[0025] Technical effects and advantages of the present invention:
[0026] The present invention adopts polydioxanone, chitin, polymethyl acrylate, glycerol, polycaprolactone, propylene oxide and polymethyl methacrylate in a specific ratio as a modified composite material, and melt blends with polylactic acid under specific conditions to achieve toughening modification of polylactic acid materials. Experiments have shown that the toughened polylactic acid blend material prepared by the present invention can effectively improve the toughness of polylactic acid and also improve its degradation rate, and has broad application prospects. DETAILED DESCRIPTION
[0027] The present invention provides a toughened polylactic acid blend, which is made from the following raw materials in parts by weight:
[0028]
[0029] It is further preferably made from the following raw materials in parts by weight:
[0030]
[0031] In the present invention, the polylactic acid, also known as polylactide (PLA), is a polyester polymer obtained by polymerization with lactic acid as the main raw material. It is a new type of biodegradable material with good solvent resistance and can be processed in a variety of ways, such as extrusion, spinning, biaxial stretching, and injection blow molding. In addition to being biodegradable, the products made of polylactic acid have good biocompatibility, gloss, transparency, feel and heat resistance. The polylactic acid used in the embodiment of the present invention is in liquid form, CAS No.: 26023-30-3, purchased from Bashifu (Shanghai) Biomedical Technology Co., Ltd.
[0032] In the present invention, the polydioxanone (PPDO) is a polyketone polymer, which is formed by a polycondensation reaction of a polydioxanone monomer, and contains a ketone group and an ester group in its chemical structure, so that the polydioxanone has high thermal stability, mechanical strength and chemical stability. The polydioxanone used in the embodiment of the present invention is in powder form, CAS No.: 31621-87-1, and is purchased from Wuhan Smack Biotechnology Co., Ltd.
[0033] In the present invention, the chitosan is a long-chain polymer, which is polymerized from N-acetylglucosamine, a derivative of glucose, as a monomer. It is a translucent, flexible, elastic and very tough substance in nature. Chitosan, also known as chitin, is a polysaccharide extracted from the shells of marine crustaceans, and its chemical formula is (C 8 H 13 O 5 N) n . Chitosan is light beige to white, soluble in concentrated hydrochloric acid, phosphoric acid, sulfuric acid and acetic acid, insoluble in alkali and other organic solvents, and insoluble in water. The deacetylated derivative of chitosan, chitosan, is insoluble in water but soluble in some dilute acids. Chitosan has a wide range of applications. In industry, it can be used to make cloth, clothing, dyes, paper and water treatment. In agriculture, it can be used as pesticides and plant antiviral agents. In fisheries, it can be used as fish feed. Cosmetic beauty agents, hair protectors, moisturizers, etc. In medical supplies, it can be used to make contact lenses, artificial skin, sutures, artificial dialysis membranes and artificial blood vessels. The chitosan used in the embodiments of the present invention is in powder form, CAS No.: 1398-61-4, purchased from Jiangsu Caiwei Biotechnology Co., Ltd.
[0034] In the present invention, the polymethyl acrylate (English name poly(methyl acrylate); Polymethacrylates) is also known as 2-methyl acrylate homopolymer (2-Propenoic acid methylester homopolymer), which is a kind of polyacrylate polymer. It is a tough, milky white, transparent, rubbery, viscous slurry material with a certain strength. It is not sticky or rarely sticky at room temperature. It is flammable, has good adhesion and elasticity, and has poor strength. It is usually soluble in acetone, ethyl acetate, dichloroethane, xylene, etc. It is insoluble in ethanol, saturated hydrocarbons, carbon tetrachloride, toluene, etc. The solubility varies with the molecular weight. The larger the molecular weight, the worse the solubility. It is a thermoplastic linear polymer. It has stable performance and is anionic; it is not resistant to strong acids, strong alkalis and electrolytes; its emulsion polymers and solution polymers are mostly copolymers. It can be used as a fabric, leather, paper treatment agent, adhesive, architectural latex paint, etc. It can also be suitable as an electrolyte for lithium batteries. The molecular formula is (C 4 H 6 O 2 ) n The polymethyl acrylate used in the embodiment of the present invention is a milky white viscous slurry, CAS number: 9003-21-8, purchased from Wuhan Kanos Technology Co., Ltd.
[0035] In the present invention, the glycerol, also known as glycerol, is an organic compound with a chemical formula of C 3 H 8 O 3 , is a simple polyol compound. It is a colorless, odorless, sweet, viscous liquid that is non-toxic. The glycerol backbone is present in lipids called glycerides. It has antibacterial and antiviral properties, is widely used in FDA-approved wound and burn treatments, and can be used as an effective marker for measuring liver disease. It is also widely used as a sweetener in the food industry and a humectant in drug formulations. Due to its three hydroxyl groups, glycerol is miscible with water and is hygroscopic; the glycerol used in the embodiments of the present invention is industrial grade, a colorless liquid; CAS number: 56-81-5, purchased from the market.
[0036] In the present invention, the polycaprolactone is an organic high molecular polymer with the chemical formula (C 6 H 10 O 2 ) n, which has the property of being well soluble in aromatic compounds, ketones and polar solvents. It is prepared by ring-opening polymerization of ε-caprolactone under the conditions of metal organic compounds (such as tetraphenyltin) as catalyst and dihydroxy or trihydroxy as initiator. It belongs to polymerized polyester, and its molecular weight and disproportionation degree vary with the type and amount of starting materials. The PCL raw material used in the embodiment of the present invention is in the form of translucent plastic particles, which is a blown film extrusion grade product purchased from Dongguan Baojia Plastic Co., Ltd.
[0037] In the present invention, the propylene oxide, also known as propylene oxide, methyl ethylene oxide, 1,2-propylene oxide, is an organic compound with a chemical formula of C 3 H 6 O is a very important raw material for organic compounds and the third largest propylene derivative after polypropylene and acrylonitrile. Propylene oxide is a colorless ether-flavored liquid with a low boiling point, flammable, and chiral. Industrial products are generally racemic mixtures of two enantiomers. It is partially miscible with water and miscible with ethanol and ether. It forms a binary azeotropic mixture with pentane, pentene, cyclopentane, cyclopentene, and dichloromethane; the propylene oxide used in the embodiment of the present invention is a colorless liquid, CAS No.: 75-56-9, and the manufacturer is Jinan Huiteng. The relevant experiments were carried out under the laboratory safety supervision and management regulations.
[0038] In the present invention, the polymethyl methacrylate (PMMA), referred to as PMMA, is a high molecular polymer, also known as acrylic or organic glass, with high transparency, low price, easy mechanical processing and other advantages, and is a commonly used glass substitute. The mechanical strength of PMMA is relatively high: the relative molecular mass of PMMA is about 2 million, it is a long-chain high molecular polymer, and the chain forming the molecule is very soft, so the strength of PMMA is relatively high, and the tensile and impact resistance is 7 to 18 times higher than that of ordinary glass. The PMMA treated by stretching can be used as bulletproof glass, and also as a canopy on military aircraft, etc.; PMMACAS No.: 9011-14-7 used in the embodiment of the present invention was purchased from Shandong Guohua Chemical Co., Ltd., and the relevant experiments were carried out under the laboratory safety supervision and management regulations.
[0039] In the present invention, the above-mentioned raw material ratio can achieve the optimal performance of the toughened polylactic acid blend, wherein too high or too low a dosage of some raw materials cannot achieve the excellent effect of the blended material of the present invention.
[0040] The present invention also provides a method for preparing the toughened polylactic acid blend, comprising the following steps:
[0041] All materials are blended to obtain a toughened polylactic acid blend; preferably, the blending is performed by melt blending; preferably, the equipment used for the melt blending is an internal mixer; preferably, the temperature of the melt blending is 130 to 180°C; preferably, the time of the melt blending is 10 to 30 minutes; the rotation speed of the melt blending is 20 to 40 rpm; preferably, extrusion molding is further performed after the blending; the thickness of the extruded molding is 0.1 to 10 mm.
[0042] The present invention also provides the use of the toughened polylactic acid blend or the toughened polylactic acid blend prepared by the above preparation method in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.
[0043] The application of the present invention in automobile manufacturing is preferably used to manufacture automobile shells, interior trims, suspension systems, engine parts, front-end modules, instrument panel frames, door modules, etc.
[0044] The application of the toughened polylactic acid blend in aerospace is preferably used to reduce weight, thereby improving fuel efficiency and load capacity, making aircraft lighter and more efficient, and to improve safety and protect internal electronic components from damage; used to enhance structural strength: the application of toughened plastics in aerospace structural parts, such as aircraft wings, fuselages, etc., can significantly improve the strength and toughness of the structure and reduce the risk of damage caused by external impact.
[0045] The toughened polylactic acid blend of the present invention is preferably used in electronic devices to enhance the mechanical properties of electronic devices and reduce the risk of damage to the devices when subjected to external impact, such as mobile phone protective cases and headphone cables, which can effectively buffer the impact and reduce the damage to the devices caused by falling or collision; used to improve safety and prevent wear and tear; used to extend the service life of electronic devices, effectively protect the internal wires from the influence of the external environment, and ensure the long-term stability and safety of the equipment
[0046] The application of the toughened polylactic acid blend of the present invention in the manufacture of industrial appliances is preferably to increase the environmental performance and service life of the appliances.
[0047] The application of the toughened polylactic acid blend of the present invention in the manufacture of packaging materials is preferably to improve brittleness: significantly reduce the brittleness of the packaging material, so that it is not easy to break during transportation and storage, and extend the service life; improve impact resistance: when subjected to external force impact, it can absorb more energy to prevent the packaging material from breaking and protect the internal items from damage; enhance durability: the packaging material can still maintain good physical properties after multiple uses, reduce the frequency of replacement, and reduce the overall cost; improve safety: it is not easy to break when impacted, reducing the safety hazards caused by the rupture of the packaging material and ensuring the safety of users.
[0048] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0049] Example 1
[0050] Weigh the following raw materials by weight and mix them evenly:
[0051]
[0052] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 150° C. for 20 min.
[0053] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0054] Example 2
[0055] Weigh the following raw materials by weight and mix them evenly:
[0056]
[0057] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 150° C. for 20 min.
[0058] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0059] Example 3
[0060] Weigh the following raw materials by weight and mix them evenly:
[0061]
[0062] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 150° C. for 25 min.
[0063] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0064] Example 4
[0065] Weigh the following raw materials by weight and mix them evenly:
[0066]
[0067] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180°C for 15 min.
[0068] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0069] Example 5
[0070] Weigh the following raw materials by weight and mix them evenly:
[0071]
[0072]
[0073] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 130° C. for 25 min.
[0074] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0075] Example 6
[0076] Weigh the following raw materials by weight and mix them evenly:
[0077]
[0078] All raw materials were put into an internal mixer for melt blending at a speed of 40 rpm and a temperature of 150° C. for 25 min.
[0079] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0080] Example 7
[0081] Weigh the following raw materials by weight and mix them evenly:
[0082]
[0083]
[0084] All raw materials were put into an internal mixer for melt blending at a speed of 20 rpm and a temperature of 150° C. for 20 min.
[0085] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0086] Comparative Example 1
[0087] Weigh the following raw materials by weight and mix them evenly:
[0088]
[0089] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 150° C. for 20 min.
[0090] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0091] Comparative Example 2
[0092] Weigh the following raw materials by weight and mix them evenly:
[0093]
[0094]
[0095] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 150° C. for 20 min.
[0096] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0097] Comparative Example 3
[0098] Weigh the following raw materials by weight and mix them evenly:
[0099]
[0100] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 150° C. for 20 min.
[0101] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0102] Comparative Example 4
[0103] Weigh the following raw materials by weight and mix them evenly:
[0104]
[0105]
[0106] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 150° C. for 20 min.
[0107] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0108] Comparative Example 5
[0109] Weigh the following raw materials by weight and mix them evenly:
[0110]
[0111] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 150° C. for 20 min.
[0112] The mixture was transferred to a single screw extruder for extrusion molding, and the thickness was set to 1 mm to obtain a toughened polylactic acid blended material.
[0113] Experimental example
[0114] The following tests were performed using pure PLA, materials obtained in Examples 1 to 6, and Comparative Examples 1 to 5 as samples:
[0115] Mechanical properties test:
[0116] Use a universal mechanical properties tester to test the tensile properties of the specimens and record the results;
[0117] The sample size is 4mm×1mm, the chuck spacing is 30mm, and the tensile speed is 5mm / min.
[0118] The samples were placed at room temperature for 48 hours before testing.
[0119] The tensile elastic modulus is tested during the tensile test. During the elastic deformation stage of the tensile test, the strain value of the sample under a specific stress is measured and the tensile elastic modulus is calculated using Hooke's law:
[0120] E = σ / ε, where E is the tensile elastic modulus, σ is stress, and ε is strain
[0121] The measurement results are shown in Table 1 below:
[0122] Table 1 Mechanical properties test results
[0123]
[0124] From the mechanical property test results, it can be seen that the toughened polylactic acid blend provided by the present invention can increase the elongation at break from 6.82% of pure PLA to 92.08%-99.26%; the tensile strength is increased from 52.13MPa of pure PLA to 111.86MPa-137.58MPa; the tensile elastic modulus is increased from 3.55GPa of pure PLA to 0.2GPa-0.38GPa, indicating that it has the excellent performance of not being easy to break or fracture when subjected to impact or pressure, and has good application prospects in the industry; and the test results also reflect that the selection of toughening and modifying raw materials in the blend and the setting of the addition amount have an important influence on the toughening effect. The use of the formula in the embodiment of the present invention can enable the blend to exert better compatibility and interaction, thereby obtaining optimal performance.
[0125] Biodegradation performance test:
[0126] With reference to GB / T19277-2003 / ISO 14855:1999 and the prior art, the biodegradability of pure polylactic acid, the materials obtained in Examples 1 to 6, and Comparative Examples 1 to 5 under composting conditions was determined.
[0127] Compost properties: pH 5.23, total nitrogen 2.64%, water content 10.02%, carbon-nitrogen ratio 31.65, organic matter content 112.80%, stir well and set aside.
[0128] The samples were cut into 1 cm × 1 cm. For each experiment, 200 g of compost and 20 g of sample were weighed, and the water content was adjusted to 60% with distilled water. After being fully mixed, they were placed in a constant temperature incubator at a temperature of (56 ± 2) °C. Soluble alkali solution was used as CO 2 After the experiment started, CO was measured every 24 hours. 2 The release amount was measured every 7 days, and the pH value of the compost was measured. The properties and structure of the compost, moisture, color, mold formation, odor of the exhaust gas, etc. were observed and recorded to ensure the smooth progress of the experiment.
[0129] Biodegradation rate calculation formula:
[0130] Dt={(CO 2 ) T -(CO 2 ) B} / ThCO 2 ×100% (1)
[0131] Where: (CO 2 ) T - Cumulative CO emissions from each compost container containing the test mixture 2 Quantity (g / container)
[0132] (CO 2 ) B - Cumulative CO released from blank container 2 Average amount (g / container)
[0133] ThCO 2 - Sample produces CO 2 Theoretical release amount (g / container)
[0134] The test was carried out for a total of 120 days, during which the biodegradation rate of each group of samples at 60 days, the number of composting days to reach the highest biodegradation rate, and the biodegradation rate of each group of samples after the test were recorded, as shown in Table 2 below:
[0135] Table 2 Biodegradation performance test results
[0136]
[0137] It can be seen from the biodegradation results that the toughened polylactic acid blend provided by the present invention can synergistically promote the hydrolysis in the degradation process, promote the penetration of water in the sample in the compost, and then improve the biodegradation efficiency, reaching the level of high degradation of 120d composting, with excellent biofriendliness, effectively reducing the impact on the environment, solving the problem of plastic pollution, and achieving sustainable development.
[0138] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A toughened polylactic acid blend, characterized in that: Made from the following raw materials in parts by weight:
2. The toughened polylactic acid blend according to claim 1, characterized in that: Made from the following raw materials in parts by weight:
3. The method for preparing the toughened polylactic acid blend according to claim 1 or 2, characterized in that: The following steps are involved: All materials are blended to obtain a toughened polylactic acid blend.
4. The preparation method according to claim 3, characterized in that: The blending is carried out by melt blending.
5. The preparation method according to claim 4, characterized in that: The equipment used in the melt blending method is an internal mixer.
6. The preparation method according to claim 4, characterized in that: The temperature of the melt blending method is 130-180°C.
7. The preparation method according to claim 4, characterized in that: The time of the melt blending method is 10 to 30 minutes.
8. The preparation method according to claim 4, characterized in that: The rotation speed of the melt blending method is 20 to 40 rpm.
9. The preparation method according to claim 3, characterized in that: The blending further includes extrusion molding; The thickness of the extrusion molding is 0.1 to 10 mm.
10. Use of the toughened polylactic acid blend according to claim 1 or 2, or the toughened polylactic acid blend prepared by the preparation method according to any one of claims 3 to 9 in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.
Citation Information
Patent Citations
Polylactic acid flexibilizer and preparation method thereof and modified polylactic acid and preparation method thereof
CN102675523B
Modification method for strengthening and toughening polylactic acid material
CN110204876A
Natural polymer / degradable polymer composite material and preparation thereof
CN101486806A
Full-degradable injection product and preparation method therefor
CN105623219A
High-toughness polylactic acid-based biodegradable material and preparation method thereof
CN113583410A
Cited By
Environment-friendly degradable polylactic acid straw and preparation process thereof
CN120137370A
Environment-friendly degradable polylactic acid straw and preparation process thereof
CN120137370B